Message - Ahmad Najib, Assoc. Prof. (Universal Journal of Pharmaceutical Research, 2024)
The Universal Journal of Pharmaceutical Research is a commendable reflection of the journal’s commitment to impactful global health research. The featured studies on innovative antileishmanial and anti-inflammatory therapies highlight the strides being made in disease treatment, while studies on medication adherence in some countries demonstrate a thoughtful approach to improving healthcare accessibility in diverse contexts. In this welcome, I will discuss the importance of presenting the author’s facial image in the journal to help global readers and research colleagues recognize them. Facial expressions play a crucial role in both conscious and unconscious emotional communication, with frowns indicating rejection and smiles suggesting happiness. The ability to interpret these expressions is foundational for empathy and understanding others’ reactions. Individual facial features contribute to emotional expression, and psychologists argue that a face is perceived holistically rather than as a collection of parts. Research indicates that certain brain regions respond more actively to faces, with differences noted between shy and sociable individuals in their brain activity when viewing unfamiliar faces. Additionally, attractive faces activate a widespread neural network related to perception, decision-making, and reward. The exploration of plant-based treatments showcases nature’s promising potential in pharmaceuticals, and the investigation into sustainable chitosan extraction practices demonstrates a forward-thinking approach to resource use. This Journal also includes timely reviews on hypertension management and stroke prevention, offering practical, evidence-based guidance for widespread health concerns, and underlining the journal’s value to both researchers and clinicians. Collectively, these articles underscore the journal’s role as a beacon for rigorous research with real-world applications that enhance patient care globally. The dedication of the contributors to expanding pharmaceutical knowledge and refining patient outcomes is truly inspiring. We hope that this edition achieves the wide recognition it deserves, inspiring further research, collaboration, and innovation that support healthier, more resilient communities